Extremely poor patient-reported outcomes are associated with lack of clinical response and decreased retention rate of tumour necrosis factor inhibitor treatment in patients with axial spondyloarthritis. (4th March 2019) - Krabbe, S; Glintborg, B; Østergaard, M; Hetland, ML
Abstract : Objective : To investigate whether axial spondyloarthritis (axSpA) patients with extremely poor patient-reported outcomes (PROs) at start of first tumour necrosis factor inhibitor (TNFi) treatment have poorer treatment response and shorter treatment retention than other patients. Method : This observational cohort study was based on the nationwide DANBIO registry. Patients with axSpA who started first TNFi during 2011–2016 were stratified according to baseline Bath Ankylosing Spondylitis Disease Activity Index (BASDAI ≥ 0.0 to ≤ 4.0, > 4.0 to ≤ 5.0, > 5.0 to ≤ 6.0, > 6.0 to ≤ 7.0, > 7.0 to ≤ 8.0, > 8.0 to ≤ 9.0, and > 9.0 to ≤ 10.0). An extremely poor BASDAI was defined as BASDAI > 9.0 to ≤ 10.0. Treatment responses after 6 months [≥ 50% improvement from baseline BASDAI (BASDAI50), ≥ 40% improvement in Assessment of SpondyloArthritis international Society (ASAS40) response, and ASAS partial remission] in patients with extremely poor PROs were compared with other patients by chi-squared tests, and retention rates by log-rank tests. Similar analyses were done for Bath Ankylosing Spondylitis Functional Index (BASFI), pain score, and patient global score. Results : The study included 1396 patients (median age 39 years, 60% men). Patients with extremely poor baseline BASDAI [63 patients (5%)] were more often women, ever smokers, and human leucocyte antigen-B27 negative, and had higher body mass index. Response rates were poorer in patients with extremely poor BASDAI vs remaining patients (BASDAI50 19% and 41%, respectively, p < 0.001; ASAS40 16% and 35%, p = 0.002; ASAS partial remission 6% and 22%, p < 0.001). Patients with extremely poor BASDAI had lower 1 year treatment retention (51% and 68%, p < 0.001). Largely similar results were found for patients with extremely poor BASFI, pain score, and patient global score. Conclusion : Patients who reported an unusually large symptom burden at baseline had poor response rates and low retention rate. In such cases, competing causes of pain should carefully be taken into account when considering treatment with TNFi.